The Impact of Electronic Management in Enhancing Knowledge Management An Applied Study - El Ghurabli, Zainab; Elsawy, Mahmoud (The Arab Journal of Administration, 2023)
The current study aims to investigate the relationship between the Electronic Management and the knowledge management at the emirate state universities. a random sample of 346 employees was chosen from the emirate state universities. A questionnaire has been used to collect the primary data, the results revealed that there is a significant positive relationship between Electronic Management and the knowledge management, and there is a significant positive relationship between Electronic Management and knowledge management dimensions The results also showed that the studied universities apply electronic management in its operations, the results also reflects the approval of the sample members that knowledge management and its dimensions is available in the studied universities. The researchers recommended various recommendations such as how employees should to take advantage of the new systems applied to facilitate their work that should be happened through training workshops and introductory seminars.